Dendritic cells and tolerance induction - STEPTOE, R J (Blackwell Science Inc, 1996)
Dendritic cells (DC) are widely accepted as the most potent antigen-presenting cells (APC), and considerable interest has been generated in their potential for the immunological therapy of cancer and infectious disease. Recently, however, a broader understanding of the phenotypic diversity and functional heterogeneity of DC has been acquired. Thus, in addition to having a role in central tolerance, DC are now regarded as potential modulators of peripheral immune responses. Harnessing this potential may offer a new approach to the immunosuppressive therapy of allograft rejection or autoimmunity. Here, the concept of ‘tolerogenic’ DC is placed in the context of rapidly accumulating new evidence of the diverse properties of these important APC.